Fixed point theorems via Nash Equilibria - Juan Pablo Torres-Martínez (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
In this note we show that the fixed points of a continuous function (or of an upper semi-continuous correspondence, with non-empty and convex values) can be attained as Nash Equilibria of a game with finitely many players.
Keywords: 330; Spieltheorie; Nash-Gleichgewicht